Recurrent Spigelian Hernia: case report - Rosati, Luís Fernando; Menezes, Flávia Martins; Figueiredo, Bruno Cesar Sabino; Oliveira, José Lucas Peixoto Costa; Chimeli-Ormonde, Luiza (Brazilian Journal of Case Reports, 2023)
The protrusion of adipose tissue, peritoneal sac or abdominal viscera in the anterolateral region of the abdomen can configure the so-called Spigelian hernia. A 53-year-old patient with comorbidities is admitted for reoperation of Spiegel’s hernia. Aging and the presence of obesity, multiparity and previous surgery may have predisposed the appearance of this type of hernia. For recurrence, obesity may have been a contributing factor, although factors related to the surgical procedure and the hernia itself should also be considered. Spiegel’s hernia is a rare abdominal hernia whose treatment is surgery, bearing in mind the risks of recurrence and the possibilities of mitigating them.